The perceptions and challenges of mathematics learning among the B40 students and parents during PdPR at SMK Bakong, Miri, Sarawak - Anak Lampas, Lin Cherida; Yong, Sharon Yee Ong; Wong, Tze Jin; Koo, Lee Feng; Mohd Fuzi, Nursyazwani; Habidin, Nurul Fadly (Human Resource Management Academic Research Society, 2023)
The surge in internet usage in Malaysia, amplified by the COVID-19 pandemic, has transformed education with a shift to virtual learning. This shift, however, has been challenging for students from the Bottom 40 (B40) income group, particularly in rural areas of Sarawak, Malaysia, due to limited internet access. This paper aims to explore the perceptions and challenges of Mathematics learning among B40 students and parents during the Home-based Learning (PdPR) at SMK Bakong, Miri. Employing the Technology Acceptance Model (TAM), we propose to study the acceptability and challenges related to Mathematics learning via ICT. The conceptual framework will be tested using statistical analysis with data collected from questionnaires. The findings from this study will help illuminate the experiences, usage patterns, and impact of online learning for B40 students and parents and identify the strengths and weaknesses of the current approach. The insights gained will be instrumental in guiding policy makers and practitioners towards improving the quality of Mathematics learning in rural areas of Sarawak during PdPR.